2014
DOI: 10.1002/aoc.3151
|View full text |Cite
|
Sign up to set email alerts
|

New nickel(II) diimine complexes bearing phenyl and sec‐phenethyl groups: synthesis, characterization and ethylene polymerization behaviour

Abstract: A series of nickel(II) catalysts containing phenyl and chiral sec-phenethyl groups, {[(4-R 1 -2-R 2 C 6 H 2 N¼C) 2 Nap]NiBr 2 } (Nap: 1,8naphthdiyl, R 1 = Me, R 2 = Ph (3a); R 1 = Me, R 2 = sec-phenethyl (3b); R 1 = Cl, R 2 = sec-phenethyl (3c); R 1 = Me, R 2 = Me (3d) were synthesized and characterized. All organic compounds were fully characterized by FT-IR and NMR spectroscopy and elemental analysis. The single crystal for X-ray crystallography was isolated from 3a in CH 2 Cl 2 /n-hexane under air; the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Et 2 AlCl and MMAO were donated by Tosoh-Finechem. Pd(II) catalyst [ 30 ], 4 [ 30 ], 5 [ 30 ], L4 [ 27 ], L5 [ 29 ], L6 [ 31 ], C4 [ 27 ], C5 [ 29 ] and C7 [ 32 ] were prepared according to the literature procedures. Other chemicals were commercially obtained and purified with common procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Et 2 AlCl and MMAO were donated by Tosoh-Finechem. Pd(II) catalyst [ 30 ], 4 [ 30 ], 5 [ 30 ], L4 [ 27 ], L5 [ 29 ], L6 [ 31 ], C4 [ 27 ], C5 [ 29 ] and C7 [ 32 ] were prepared according to the literature procedures. Other chemicals were commercially obtained and purified with common procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that bulky chiral ortho-sec- diphenethyl-substituted [ 25 , 26 ] and ortho- phenyl substituted [ 27 , 28 , 29 ] α-diimine Ni(II) and Pd(II) complexes that exhibited high activities towards ethylene polymerization and produced highly-branched polyethylene upon activation with Et 2 AlCl. In this context, we have become very interested in phenyl-substituted α-diimine ligand Ni(II) precursors for polymerization of ethylene and 1-alkenes at the different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that bulky ortho‐sec‐ phenethyl ‐ substituted and ortho‐ phenyl substituted α‐ diimine nickel and palladium complexes exhibited high activities toward ethylene polymerization and produced highly branched polyethylene upon activation with Et 2 AlCl or MMAO, and also produced branched poly(1‐alkene)s with high molecular weight. We anticipated that bulky α‐ diimine ligands might control chain walking and produce regioregular polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Our group showed recently that fast chain‐walking process in α‐ diimine based nickel system can be efficiently modulated via the introduction of phenyl substituents . Consequently, these phenyl‐substituted complexes catalyzed ethylene, linear 1 ‐, 2 ‐ olefin and 4 ‐ octene polymerizations to afford high molecular weight polymers with different branching structures and demonstrated living behavior at low temperature. In this work, we report the polymerization of 4MP using a series of phenyl‐substituted α‐ diimine nickel catalysts in combination with Et 2 AlCl, and investigated the effects of catalyst structure and polymerization temperature on branching degree and insertion pathways.…”
Section: Introductionmentioning
confidence: 99%